Occupational burnout during war: The role of stress, disruptions in routine, sleep, work-family conflict, and organizational support as a moderator - Maor Kalfon Hakhmigari; Irene Diamant (PLoS ONE, 2025)
Background Occupational burnout, resulting from long-term exposure to work-related stressors, is a significant risk factor for both physical and mental health of employees. Most research on burnout focuses on routine situations, with less attention given to its causes and manifestations during prolonged national crises such as war. According to the Conservation of Resources theory, wartime conditions are associated with a loss of resources, leading to accelerated burnout. This study aimed to examine burnout among employees during the war in Israel that broke out in October 2023, placing the population nationwide in a state of existential threat and functional crisis. The researchers hypothesized that Stress, work-to-family conflict, family-to-work conflict, sleep disruption, and routine disruption (H1-H5) would be positively associated with occupational burnout. In addition, the study examined whether organizational strategies, such as flexibility and volunteering, would be negatively associated with burnout (H6) and whether they would moderate the relationship between work-family conflict and burnout during wartime (H7). Methods The study involved 374 employees recruited through social networks via a snowball sampling method during the war. Participants completed a questionnaire assessing demographic details, burnout, stress, routine disruptions, work family conflict (work-to-family and family-to-work conflict), sleep disturbances, and organizational support measures. Hierarchical linear regression and Pearson correlation were utilized to model the outcome variable of occupational burnout and Process Model 1 was utilized for the moderation hypothesis. Results Findings revealed a notable level of burnout during wartime (M = 3.95, SD = 1.15). Routine disruptions, work-to-family conflict, and sleep disturbances significantly contributed to burnout beyond stress levels, thus hypotheses H1 to H5 were partly supported. Additionally, the organizational resource variable of offering volunteering opportunities was associated with lower burnout levels and moderated the relationship between work-to-family conflict and burnout, thus partially supporting hypotheses H6 and H7. Conclusion The findings enhance the understanding of burnout during prolonged crises like war, highlighting the importance of maintaining routine as a key resource for order and control. They also emphasize the role of organizational volunteering in preventing burnout. The theoretical and practical implications are discussed.